Using a Vibrotactile Biofeedback Device to Augment Foot Pressure During Walking in Healthy Older Adults: A Brief Report - Yasuda, Kazuhiro; Hayashi, Yuki; Tawara, Anna; Iwata, Hiroyasu (Frontiers in Psychology, 2019)
Human movement based on sensory control is significant to motor task performance. Thus, impairments to sensory input significantly limit feedback-type motor control. The present study introduces a vibrotactile Biofeedback (BF) system which augments information regarding the user’s foot pressure to enhance gait performance. We evaluated the influence of the proposed system on gait pattern in healthy older adults and attempted to determine its effect on cognitive load during gait; these factors are essential to clarify feasibility of the device in real-life settings. The primary task of our study was to evaluate gait along with a cognitively demanding activity. We studied 10 healthy older adults. Regarding walking ability in the BF condition, participants extended their stride length, which was sustained by increasing the ankle joint angle at the heel contact phase and foot pressure at the toe off. However, these kinematic changes did not contribute to increased walking speed. In addition, cognitive performance (i.e., the number of correct answers) was significantly decreased in participants during gait measurements in the BF condition. These results suggest that the system had the potential to modify the kinematic pattern but not the walking speed in older adults. Moreover, the device appears to place a cognitive load on older adults. This brief report provides essential preliminary data for designing successful sensory augmentation devices and future research trials with a BF system.